Leaving the fish bowl: the ornamental trade as a global vector for freshwater fish invasions. Issue 4 (2nd October 2019) - Chan, Farrah T.; Beatty, Stephen J.; Gilles, Allan S.; Hill, Jeffrey E.; Kozic, Sebastian; Luo, Du; Morgan, David L.; Pavia, Richard T. B.; Therriault, Thomas W.; Verreycken, Hugo; Vilizzi, Lorenzo; Wei, Hui; et al.
Abstract : Despite its social and economic benefits, the trade in ornamental species (henceforth, 'ornamental trade') has become a major source of non-native fish introductions into freshwater ecosystems. However, the ornamental trade as a vector for introductions of non-native freshwater fishes is not well defined. We developed a framework incorporating elements of the biological invasion process and a typical ornamental fish trade supply chain to fill this gap. Records of non-native ornamental fishes introduced to freshwater environments of Australia, Belgium (Flanders), Canada (British Columbia), China (Guangdong), the Philippines, Poland, Singapore, the United Kingdom (England), and the United States of America (Florida) were reviewed to explore the pervasiveness of these introduced fishes in the wild. These regional case studies confirmed the prominence of the ornamental trade as a global vector for freshwater fish introductions beyond their natural range. Additionally, we examined freshwater fishes associated with the ornamental trade to identify 'risky' species that could establish in recipient regions based on climate match. All regions assessed were at risk of new fish introductions via the ornamental trade, with the number of 'risky' species ranging from seven to 256. Further, there appears to be taxonomic bias in the freshwater ornamental fish trade, with 74% of the species belonging to just 10 families (of 67). Current prevention and management approaches and associated polices, regulations and legislation on aquatic non-native species within assessed regions fit five general categories: import controls, risk assessment, whitelist, blacklist, and release ban. However, these prevention/management efforts may not be sufficient to reduce the invasion risk associated with the ornamental fish trade. Recommendations including species- and vector-based risk assessments, better recording of species import consignments, increased public education and industry engagement, and early detection and rapid response are discussed in this review.